Protocol for the maintenance of strains and escalation in the production of microalgae of industrial interest (2021)
Scenedesmus sp. & Chlorella sp., are two isolated microalgae from hot springs located in Norte de Santander, which are studied in order to explore their biotechnological potential. The present work aimed to design a protocol by evaluating two factors, the effect of light radiation stress and incubation time by staggering the culture from box to tube with 20 mL of medium and finally in a 200 mL reactor. From this, in order to obtain a higher production of carotenoids of industrial interest, therefore, a non-factorial central composite surface design was used; As results, it was determined that in Scenedesmus spmicroalgae the two factors influence carotenoid deposition and for Chlorella spthe incubation time does not influence and the photoperiod is fundamental in the deposition of thesemetabolites, on the other hand the program in which evaluated the STATISTICA 7.0 design generates its respective equation from which the optimal incubation time and photoperiod for the studied microalgae were determined